Chapter 6: Linguistically Innovative Poetry 1978-2000. - SHEPPARD, ROBERT (Poetry of Saying: British Poetry & Its Discontents, 1950-2000, 2005)
Chapter 6 of the book "The Poetry of Saying: British Poetry and Its Discontents, 1950-2000" is presented. It explores the origins of Linguistic Innovative Poetry of the 1990s as a phrase specifying a work for which a satisfactory name has not been given. It highlights the literary works in the post-1977 conditions of poetry with low publishing opportunities and looking towards the Movement orthodoxy and the broader literary world.